A multi-perspective approach to the evaluation of a multi-user system in the field of TEL. (7th June 2010) - Bottino, Rosa Maria; Ott, Michela; Pozzi, Francesca
The present contribution tackles the issue of the evaluation of models and systems in the field of technology enhanced learning (TEL), with specific reference to pedagogical planning. It presents an evaluation model designed to evaluate the work carried out by the authors in the framework of the EU project ReMath, where a web-based pedagogical planner was produced, in compliance with a theoretical model adopting an innovative approach to pedagogical design. During this project, while allowing the evaluation of the research results, the need to evaluate separately the different elements underlying the system clearly emerged (theoretical model and implemented tool) and also to carry out its evaluation from multiple standpoints by assuming the perspectives of the different categories of users: plan authors, readers and experimenters. The adopted evaluation model proved to be able to highlight the strengths and weaknesses of the TEL system at hand, by distinguishing between theory and practice, between the advantages and disadvantages derived from the theoretical model and/or those referable to the implemented tool.